Control of criminal repetition: recidivism - Cristobal Jiménez, Martin Jesus (2024)
The present work analyzes the different pronouncements regarding the institute of recidivism in order to identify each of the elements that make up said institute in order to establish the necessary elements to configure recidivism at present, within the framework of current law, analyzing in an exhaustive manner the interpretation that has been given to said institute, regarding the concurrence of a custodial sentence of an effective nature, and the release of the agent of the penitentiary establishment in which he was interned, as well as the pronouncements that ratify the constitutionality of the institute of recidivism.